Low-dose short-course metformin decrease the risk of atherosclerosis in the non-obese prediabetic individuals - Djoko Hardiman, Djoko Hardiman (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: The establishment of macrovascular (cardiovascular) event is initiated in the period of prediabetic. Metformin plays role in the carbohydrate and lipid metabolism as well as vascular protection. The mechanism of the cardiovascular event risk increased in the pre-diabetic individual has not been clearly established.Objective: The study was to determine if insulin resistance control by low-dose short-course metformin administration in the non-obese prediabetic individual might decrease the risk of atherosclerosis.Methods: It was a prospective experimental double blind study with pretest-posttest control group design. It was conducted on the first degree relatives of type-2 Diabetes Mellitus patients who met the criteria of non-obese prediabetic individuals. Subjects were randomly classified into treatment group (designed for metformin administration), and the control group (designed for placebo administration). The prediction of atherosclerosis risk was based on the hsCRP, PAI-1, VCAM-1, and fibrinogen levels.Result: The results showed that the margin between pre- and post-metformin administration term were 1.89 vs. 0.06 mg/L (p=0.001), 1.42 vs. 0.84 IU/mL (p=0.0151. 180.85 vs. 03.81 mg/L (p=0.061) and 80.15 vs. 31.42 mg/dL (p=0.001) for hsCRP, PAI-1, VCAM-1, and Fibrinogen levels in the treatment and control group, respectively.Conclusion: The study concluded that the low-dose short-course metformin administration might decrease the atherosclerosis risk significantly in the non-obese prediabetic individuals.Key words: metformin - non-obese prediabetics - hsCRP - PAI-T- Fibrinogen - VCAM-T